Kualitas Fisik Sosis Telur Itik Dengan Penambahan Wortel (Daucus Carota L.) - Daryanto Daryanto; Metha Monica; Fatati Fatati (Jurnal Ilmu Peternakan Indonesia, 2026)
This study aims to determine the effect of adding various concentrations of carrots (Daucus carota L.) on the physical quality of duck egg sausages including water content, cooking loss, and pH. The study was conducted at the Laboratory of the Faculty of Animal Husbandry, Jambi University on November 24–28, 2025. The research method used was an experiment with a Completely Randomized Design (CRD) consisting of 5 treatments and 4 replications. The treatments given were the addition of carrots as much as 25% (P1), 35% (P2), 45% (P3), 55% (P4), and 65% (P5) with the use of sago flour of 10% in each treatment. Data were analyzed using analysis of variance (ANOVA) and continued with Duncan's test if  there  were  significant differences. The results of  the  analysis  of  variance showed  that  the  addition of  various concentrations of carrots had no significant effect (P>0.05) on the water content and cooking loss of duck egg sausages, but had a significant effect (P<0.01) on the pH value. The water content ranged from 61.44–65.54% and cooking loss between 3.09–8.05%. Treatment P3 produced the lowest cooking loss (3.09%) with the lowest water content (64.45%) and pH (7.13). Based on the results of the parameters, treatment P3 (45% carrot addition) produced good physical quality and showed significantly lower results compared to the other treatments.